2012
DOI: 10.1371/journal.ppat.1002844
|View full text |Cite
|
Sign up to set email alerts
|

High Virulence of Wolbachia after Host Switching: When Autophagy Hurts

Abstract: Wolbachia are widespread endosymbionts found in a large variety of arthropods. While these bacteria are generally transmitted vertically and exhibit weak virulence in their native hosts, a growing number of studies suggests that horizontal transfers of Wolbachia to new host species also occur frequently in nature. In transfer situations, virulence variations can be predicted since hosts and symbionts are not adapted to each other. Here, we describe a situation where a Wolbachia strain (wVulC) becomes a pathoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
84
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(95 citation statements)
references
References 45 publications
5
84
0
Order By: Relevance
“…There is evidence that multiple host mechanisms may be involved in inhibiting viral replication including synthesis of reactive oxygen and cholesterol and induction of host autophagy (Le Clec'h et al 2012;Pan et al 2012;Caragata et al 2013;Wong et al 2015). Our finding that Wolbachia dramatically alters host ER morphology and relies on the ERAD pathway to maintain titer suggests the involvement of a previously unsuspected mechanism in preventing the replication of positive-strand RNA viruses.…”
Section: Discussionmentioning
confidence: 77%
“…There is evidence that multiple host mechanisms may be involved in inhibiting viral replication including synthesis of reactive oxygen and cholesterol and induction of host autophagy (Le Clec'h et al 2012;Pan et al 2012;Caragata et al 2013;Wong et al 2015). Our finding that Wolbachia dramatically alters host ER morphology and relies on the ERAD pathway to maintain titer suggests the involvement of a previously unsuspected mechanism in preventing the replication of positive-strand RNA viruses.…”
Section: Discussionmentioning
confidence: 77%
“…This constitutive aspect of immunity, defined early in development will continue to have real effects on the performance of phagocytosis in the adult [63]. Also, the recent transinfection of Wolbachia into new insect hosts has been associated with increases in autophagy [64] and the generation of reactive oxygen species [65], both of which may not be captured in transcriptional measures.…”
Section: Discussionmentioning
confidence: 99%
“…This protocol was applied to inject three separate batches of individuals. Previous studies revealed that wVulC injections in A. vulgare females had no effect on different life history traits (Le Clec'h et al, 2012). The animals were then used for behavioral assays 6 months post-injection, leaving enough time for Wolbachia to spread and be incorporated into the host tissue, as is the case in naturally infected individuals (Juchault and Mocquard, 1989).…”
Section: Artificial Infection With Wolbachiamentioning
confidence: 99%
“…In general, Wolbachia are weakly virulent to their native hosts (Engelstädter and Hurst, 2009), probably as a result of the host/parasite coevolution of the vertical transmission process (Lipsitch et al, 1996;Engelstädter and Hurst, 2009), although the symbiotic bacteria may become pathogenic when bacterial levels get too high (Sachs and Simms, 2006;Le Clec'h et al, 2012). However, although Wolbachia affects the mating choice through CI of its host in some Drosophila (Moreau et al, 2001;Markov et al, 2009;Sharon et al, 2010), this is not always true for all Drosophila species (Jenkins et al, 1996;Sullivan and Jaenike, 2006).…”
Section: Introductionmentioning
confidence: 99%